A cunning State control – an unprecedented regulatory challenge brought forward by the Chinese social media giant "WeChat" - Grace Li (International Telecommunications Society (ITS), 2018)
China is the largest country by smart phone user and Internet user. By 2017, China has over 1 billion smart phone users and over 70% of its entire population having access to the Internet.1 With severe State censorship and the Great Firewall of China, the worldwide social-media platforms such as Facebook and Tweeter are not accessible in China. This situation has created great opportunities for Chinese companies to generate China's own version of its social media platforms – WeChat, a mobile based, all-purpose social media application has become the answer. Developed by Chinese multinational investment holding conglomerate Tencent, WeChat originally started in 2010 with a Chinese name "Weixin" (literally meaning "micro-message")2. WeChat quickly rose in popularity and the number of active users has reached over one billion in March 2018,3 which means almost every single smart phone user in China would had WeChat installed in their device. Unlike itsWestern counterparts, Facebook Messenger and WhatsApp, WeChat's features were not only limited to Internet messaging. Apart from messaging, voice and video calls, WeChat also offered services such as digital wallet payments, booking doctor appointments, booking taxi and paying electricity bills under the WeChat City Services4, crowd density map used by the government5, reading news, play games, and many more. As WeChat has developed into the China's all-in-one app, dominate proportion of Chinese smartphone users are now less likely dependent on any other apps and solely rely on WeChat for everything...
Keywords: 330